2021
DOI: 10.1039/d1gc00851j
|View full text |Cite
|
Sign up to set email alerts
|

Separation of short-chain glucan oligomers from molten salt hydrate and hydrolysis to glucose

Abstract: Selective production of glucose from hydrolysis of cellulose is the key step for efficient utilization of lignocellulose biomass. Crystalline cellulose can be dissolved and hydrolyzed into glucose with a high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…The produced sugars, MSH and methanol can be readily separated and recycled in commercial ways. 17 It was found that after being treated using this stepwise method, the yield of glucan oligomers produced from corn stover hydrolysis remarkably increased from 59.9% to 79.5% and the separation efficiency also increased from 54.2% to 80.6%, suggesting potential applications in lignocellulose valorization as the value-added chemical in healthcare 29,30 and agriculture. 31,32 Crystalline cellulose (99%), glucose (99.9%), xylose (99.9%), 5-hydroxymethylfurfural (5-HMF, 99%), levulinic acid (99.9%), tetrahydrofuran (TOF, 99%) and anhydrous pyridine (99.8%) were bought from Aladdin Chemical Co., Ltd, China.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The produced sugars, MSH and methanol can be readily separated and recycled in commercial ways. 17 It was found that after being treated using this stepwise method, the yield of glucan oligomers produced from corn stover hydrolysis remarkably increased from 59.9% to 79.5% and the separation efficiency also increased from 54.2% to 80.6%, suggesting potential applications in lignocellulose valorization as the value-added chemical in healthcare 29,30 and agriculture. 31,32 Crystalline cellulose (99%), glucose (99.9%), xylose (99.9%), 5-hydroxymethylfurfural (5-HMF, 99%), levulinic acid (99.9%), tetrahydrofuran (TOF, 99%) and anhydrous pyridine (99.8%) were bought from Aladdin Chemical Co., Ltd, China.…”
Section: Introductionmentioning
confidence: 89%
“…11 The formed glucan oligomers can be readily separated from the MSHs via adsorption using amorphous carbon 11 or anti-solvent precipitation. 17 The separated glucan oligomer can be selectively hydrolyzed into glucose with a high yield under mild conditions. Under optimized conditions, a 90.4% yield of glucan oligomers can be obtained from cellulose in 60 wt% LiBr at 130 °C for 5 h without catalysts, 11 and the formed products can be precipitated out of the MSH using methanol as an anti-solvent with a high efficiency of 90.3%, 17 which is much more efficient than the separation of glucose from the MSH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selectivity to oligomer, however, decreases to 44.0% when the cellulose concentration increases to 188.2 mg mL –1 . The reduced selectivity to oligomer is likely due to the formation of byproducts including 5-hydroxymethylfurfural (5-HMF), levulinic acid (LA), and formic acid (FA). The formation of byproducts not only decreases the yield to the glucan oligomers but also catalyzes other nonselective reactions to form humins.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we have shown that the oligomers can be separated by cyclic temperature swing adsorption− desorption processes using amorphous carbon. 17 Moreover, glucan oligomers can be separated by precipitation using antisolvent 18 and a nanofiltration method.…”
Section: ■ Introductionmentioning
confidence: 99%